(untitled) (Bangladesh Journal of Botany, 2021)
The effects of application of calcium-containing natural fertilizer on the functional state of the tea plant were studied. Application of calcium resulted weakening of the negative effects of high temperatures and water deficiency due to an increase in its heat resistance (on average by 30 - 40%), an increase in catalase activity (on average 5 - 10 %), as well as adaptive rearrangement of pigment ratio to increasing the content of carotenoids, chlorophylls and the their functional activity. In general, the more efficient functioning of the signaling intracellular network due to the calcium application provided better adaptability of plants to extreme conditions and more efficient recovery after subsequent rehydration, which in a whole contributed to an increase in shoot growth activity (on average 20%) and an increase in yield by an average of 27 - 33%.